KALA ROBOT MASUK KELAS IPA: MEMBEDAH KEGAGAPAN DAN KESULITAN GURU SMP DALAM IMPLEMENTASI STEM ROBOTIK - Kurniawan, Noval; Zulirfan; Yennita; Rahmad, Muhammad; Kartika, Sania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of technology in the digital era necessitates the integration of STEM in education to develop students' 21st-century competencies. Robotics has emerged as a promising teaching media for STEM learning; however, its implementation still faces considerable challenges. This quantitative survey study aims to analyze the difficulties faced by junior high school science teachers in implementing robotics-based STEM learning and to examine whether these difficulties differ significantly based on teaching experience. A total of 27 science teachers in Tualang District, Siak Regency, were selected through purposive sampling. Data were collected using a validated 28-item Likert-scale questionnaire and converted from ordinal to interval scale using the Method of Successive Interval (MSI). Descriptive analysis revealed high levels of difficulty across all variables: Teacher Readiness (Mean = 2.78), Equipment Completeness (Mean = 2.66), and Training & Workshops (Mean = 2.75). The most critical barrier was the availability of media, modules, and budget (Mean = 2.27). Inferential analysis using the Independent Samples t-test (unequal variances assumed) showed no significant difference between junior (<10 years) and senior (≥10 years) teachers (t = −0.962, p = 0.345 > 0.05), with a small effect size (Cohen's d = 0.35). These findings indicate that robotics-based STEM implementation is a structural challenge affecting all teachers regardless of seniority, necessitating systematic support including standard robotics kit procurement, practical instructional modules, and sustained professional development programs.